Nicotinamide mononucleotide promotes female germline stem cell proliferation by activating the H4K16ac-Hmgb1-Fyn-PLD signaling pathway through epigenetic remodeling - Hong Zhou; Yujie Liu; Geng G. Tian; Ji Wu (Cell & Bioscience)
Abstract Background Nicotinamide mononucleotide (NMN), an endogenous nucleotide essential for various physiological processes, has an unclear role and regulatory mechanisms in female germline stem cell (FGSC) development. Results We demonstrate that NMN significantly enhances FGSC viability and proliferation. Quantitative acetylation proteomics revealed that NMN markedly increases the acetylation of histone H4 at lysine 16 (H4K16ac). Subsequent chromatin immunoprecipitation sequencing (ChIP-seq) and RNA sequencing (RNA-seq) identified high mobility group box 1 (Hmgb1) as a downstream target of H4K16ac, a finding further validated by ChIP-qPCR. Knockdown of Hmgb1 reduced FGSC proliferation by disrupting cell cycle progression, inducing apoptosis, and decreasing chromatin accessibility. High-throughput chromosome conformation capture (Hi-C) analysis showed that Hmgb1 knockdown induced A/B compartment switching, increased the number of topologically associating domains (TADs), and decreased chromatin loop formation in FGSCs. Notably, the chromatin loop at the promoter region of Fyn proto-oncogene (Fyn) disappeared following Hmgb1 knockdown. ChIP-qPCR and dual-luciferase reporter assays further confirmed the interaction between Hmgb1 and the Fyn promoter. Importantly, Fyn overexpression reversed the inhibitory effects of Hmgb1 knockdown on FGSC proliferation. Proteomic analysis suggested this rescue was mediated through the phospholipase D (PLD) signaling pathway, as Fyn overexpression selectively enhanced the phosphorylation of PLD1 at threonine 147 without affecting serine 561. Furthermore, treatment with 5-fluoro-2-indolyldechlorohaloamide, a PLD inhibitor, nullified the pro-proliferative effects of Fyn overexpression. Conclusions Our findings reveal that NMN promotes FGSC proliferation by activating the H4K16ac-Hmgb1-Fyn-PLD signaling pathway through epigenetic remodeling. These results deepen our understanding of FGSC proliferation and highlight potential therapeutic avenues for advancing FGSC applications in reproductive medicine.